The Role of Executive Functions in the Control of Aggressive Behavior - Krämer, Ulrike M.; Kopyciok, Robert P.; Richter, Sylvia; Rodriguez-Fornells, Antoni; Münte, Thomas F. (Frontiers in Psychology, 2011)
An extensive literature suggests a link between executive functions and aggressive behavior in humans, pointing mostly to an inverse relationship, i.e. increased tendencies towards aggression in individuals scoring low on executive function tests. This literature is limited, though, in terms of the groups studied and the measures of executive functions. In this paper, we present data from two studies addressing these issues. In a first behavioral study, we asked whether high trait aggressiveness is related to reduced executive functions. A sample of over 600 students performed in an extensive behavioral test-battery including paradigms addressing executive functions such as the Eriksen Flanker task, Stroop task, n-back task and Tower of London. High trait aggressive participants were found to have a significantly reduced latency score in the Tower of London, indicating more impulsive behavior compared to low trait aggressive participants. No other differences were detected. In an EEG-study, we assessed neural and behavioral correlates of error monitoring and response inhibition in participants who were characterized based on their laboratory-induced aggressive behavior in a competitive reaction time task. Participants who retaliated more in the aggression paradigm and had reduced frontal activity when being provoked did not, however, show any reduction in behavioral or neural correlates of executive control compared to the more aggressive participants. Our results question a strong relationship between aggression and executive functions at least for healthy, high-functioning people.